Associations of physical fitness with cortical inhibition and excitation in adolescents and young adults - Skog, Hanna Mari; Määttä, Sara; Säisänen, Laura; Lakka, Timo A.; Haapala, Eero A. (Frontiers in Neuroscience, 2024)
Objective: We investigated the longitudinal associations of cumulative motor fitness, muscular strength, and cardiorespiratory fitness (CRF) from childhood to adolescence with cortical excitability and inhibition in adolescence. The other objective was to determine cross-sectional associations of motor fitness and muscular strength with brain function in adolescence.: In 45 healthy adolescents (25 girls, 20 boys) aged 16-19 years, we assessed cortical excitability and inhibition by navigated transcranial magnetic stimulation (nTMS), and motor fitness by 50-meter shuttle run test and Box and block test and muscular strength by Standing long jump test. These measures of physical fitness and cardiorespiratory fitness (CRF) by maximal exercise were assessed also at the ages 7-9, 9-11, and 15-17 years. Cumulative measures of physical measures were computed by summing up sample-specific z-scores at ages 7-9, 9-11, and 15-17 years.Results: Higher cumulative motor fitness performance from childhood to adolescence was associated with lower right hemisphere resting motor threshold (rMT), lower silent period threshold (SPt), and lower motor evoked potential (MEP) amplitude in boys. Better childhood-toadolescence cumulative CRF was also associated with longer silent period (SP) duration in boys and higher MEP amplitude in girls. Cross-sectionally in adolescence, better motor fitness and better muscular strength were associated with lower left and right rMT among boys and better motor fitness was associated with higher MEP amplitude and better muscular strength with lower SPt among girls.2 Conclusion: Physical fitness from childhood to adolescence modifies cortical excitability and inhibition in adolescence. Motor fitness and muscular strength were associated with motor cortical excitability and inhibition. The associations were selective for specific TMS indices and findings were sex-dependent.